Gaya Kepemimpinan dan Motivasi terhadap Kinerja Karyawan di PT. TI Matsuoka Winner Industry - Maya Lolita; Alleta Dewi Maria Th (Mahesa Research Center, 2024)
This article aims to analyze the impact of leadership style, work motivation, and work discipline on employee performance at PT. TI Matsuoka Winner Industry. The focus of this research is to evaluate the contribution of these three factors to improving employee productivity. Leadership style is measured based on the situational leadership model, work motivation is assessed using Herzberg's motivation theory, and work discipline is defined by management principles that emphasize punctuality and consistency in task execution. Data was collected through a survey of 110 employees using a structured questionnaire and analyzed using multiple regression techniques. The results show that effective leadership style, high work motivation, and good work discipline significantly positively impact employee performance. However, this study has limitations, such as the small sample size and the failure to consider external factors that could influence employee performance. Therefore, it is recommended that the company conduct managerial training to improve leadership skills, design more relevant and personalized motivation programs, and strengthen work discipline policies through fair rewards and sanctions. These recommendations are expected to enhance overall employee performance and support the achievement of the company's goals.